Deconstructing AMO framework: a systematic review - Marin-Garcia, Juan A; Martinez Tomas, Juan (Intangible capital, 2016)
Purpose: The AMO framework has been widely accepted in HRM literature for explaining the linkage between human resources practices and performance. However, it remains unclear whether this model has been fully demonstrated or not. Hence, we propose a systematic review that aims at identifying those investigations that have thoroughly tested the model, as well as the approaches used by them. Design/methodology: Systematic literature review, filtering scientific papers published in journals indexed in Scopus, Web of Science or Google Scholar, from the year 1993 to 2016, in the field of Social Sciences and Humanities with research that indirectly apply the AMO model in their analysis. Findings: AMO model is an excellent and structured framework that provides a better understanding of the relationship between HRM and performance. Moreover, the effectiveness of the model's proposal appears to be beyond doubt. In fact, a well trained and skilled employee will perform better, and a motivated worker will be ready to go the extra mile. Likewise, if the work environment does not provide adequate opportunities, both abilities and motivation might become meaningless. However, we consider that many other factors could influence the positive effects of HPWS. As a matter of fact, not only contextual factors, but also individual beliefs, personal affinities, or personal circumstances (among others) might affect the implementation of these practices and the subsequent outcomes. For this reason, we consider that developing an HRM model that perfectly fit any situation is a very complicated, if not impossible, task. Research limitations/implications: The results show a significant variability in both research approaches and variables taken into consideration. In addition, it seems that little research has been conducted to verify the AMO model directly. Therefore, we consider that there is a great need to study the model from a more systematic perspective. A thorough understanding of the model could lead to a better understanding of the problems that organizations face when implementing human resource practices. Originality/value: Our study shed light on some aspects of the AMO framework within the HRM context. Specifically, we aimed to identify whether or not it is possible to confirm the model as it was originally proposed. We also find out which HR practices and measures of performance were considered across investigations, to define a standard approach.